Reward Dependence-Moderated Noradrenergic and Hormonal Responses During Noncompetitive and Competitive Physical Activities - Nagy, Zsófia; Karsai, István; Nagy, Tamás; Kátai, Emese; Miseta, Attila; Fazekas, Gábor; Láng, András; Kocsor, Ferenc; Kállai, János (Frontiers in Behavioral Neuroscience, 2022)
The aim of our study was to reveal whether increased reward dependence (RD) plays a role in the catecholamine neurotransmitter release and testosterone hormone regulation during physical activities among healthy trained participants. Twenty-two males (mean age: 40.27; ± 5.4) participated in the study. Two conditions were constructed: a non-competitive and a competitive running task (RT) which were separated by a two-week interval. Urine and blood samples were collected prior to and following the running tasks. Noradrenaline (NA), adrenaline (A), dopamine (D) and their metabolites; vanillylmandelic acid (VMA) and homovanillic acid (HVA) were measured from urine while testosterone levels were analyzed from blood samples. Reward dependence (RD) was assessed using the Cloninger’s Personality Inventory (PI). Mental health was evaluated using the WHO Well–being, Beck Depression, and Perceived Life Stress Questionnaires. According to our findings, levels of NA, A, D, VMA and testosterone released underwent an increase following physical exertion, independently from the competitive condition of the RT, while HVA levels experienced a decrease. However, we found that testosterone levels showed a significantly lower tendency to elevate in the competitive RT, compared with the non-competitive condition (p=0.02). In contrast, HVA values were higher in the competitive, compared with the non-competitive condition (p=0.031), both before and after the exercise. Considering the factor RD, in non-competitive RT, its higher values were associated with elevated NA levels (p=0.007), however, this correlation could not be detected during the competitive condition (p=0.233). Conclusion: Among male runners, the NA and testosterone levels could be predicted to the degree of reward dependence by analyzing competitive and non-competitive physical exercises.